Kriteria Memilih Wanita yang Akan Dinikahi dalam Perspektif Hadis - Najib, Afifun Najib (Cv. Kalimasada Group, 2025)
The research entitled criteria for choosing a woman to marry from the perspective of hadith is a normative-explanatory research that attempts to study, explain or describe qualitatively-descriptively with a textual and contextual approach. Data were obtained through literature studies focusing on one particular hadith. Data analysis was carried out by studying the text of the hadith and the text of the verses of the Qur'an and connecting them contextually in the field. The findings of the study indicate that the criteria for choosing a woman to marry from the perspective of hadith can be studied textually and contextually. From the textual perspective of hadith, there are 4 criteria for choosing a woman as a prospective wife. While from the contextual perspective, the criteria for choosing a woman as a prospective wife who brings benefits to a male suitor. The conclusion of the study, the best criteria are seen from her religion as Abu Hurairah's friend narrated the hadith from the Messenger of Allah regarding this matter, namely 4 things: because of her wealth, because of her lineage, because of her beauty, and because of her religion. The most important thing is to choose a woman who has a good and perfect religion, then you will be lucky. The woman who will be married is one who is religious and is the right choice to be prioritized over the other 3 criteria.